The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1984
DOI: 10.1107/s0108767384001616
|View full text |Cite
|
Sign up to set email alerts
|

Electronic and atomic collisions: invited papersedited by J. Eichler, I. V. Hertel and N. Stolterfoht

Abstract: Books Received The following books have been received by the Editor. Brief and generally uncritical notices are given of works of marginal crystallographic interest; occasionally a book of fundamental interest is included under this heading because of difficulty in finding a suitable reviewer without great delay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1985
1985
2000
2000

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Since then it has developed into a very flourishing and stimulating branch of atomic collision physics. Several reviews on the subject give a comprehensive survey on the present status of this field of research (Blum and Kleinpoppen 1979, 1983a, b, Andersen and Nielson 1982, Slevin 1984, Andersen and Neitzke 1984. Briefly, these experiments are very similar to the method of perturbed angular correlations in nuclear physics.…”
Section: General Context and Some Recent Developrnents In Collision P...mentioning
confidence: 99%
“…Since then it has developed into a very flourishing and stimulating branch of atomic collision physics. Several reviews on the subject give a comprehensive survey on the present status of this field of research (Blum and Kleinpoppen 1979, 1983a, b, Andersen and Nielson 1982, Slevin 1984, Andersen and Neitzke 1984. Briefly, these experiments are very similar to the method of perturbed angular correlations in nuclear physics.…”
Section: General Context and Some Recent Developrnents In Collision P...mentioning
confidence: 99%
“…The Ar + ions registered by the mass spectrometer can be the result of ionization in the mass spectrometer ionizer of both the single atoms and clusters due to intensive boiling of clusters after ionization. Haberland [15,16] has shown that, after electron impact ionization of a rare gas cluster, the positive charge, which is delocalized at first, is localized after about 10 −12 s in a dimer ion. The relaxation of its binding energy (about 1 eV) can lead to the cluster fragmentation.…”
Section: Argon Pulsed Jets In the Distant Zonementioning
confidence: 99%